Feasible power-flow solution analysis of DC microgrids under droop control - Liu, Zhangjie (2022)
DC Microgrids have been widely used due to their high efficiency, high reliability and flexibility. A sine qua non condition for the correct operation of systems is the existence of a feasible power-flow solution. This paper analyzes the existence of the feasible power-flow solution of the DC microgrid under droop control. Firstly, the power-flow mathematical model of DC microgrid is established. Then, based on the nested interval theorem, we obtain the sufficient conditions of the existence of the feasible power-flow solution, and the uniqueness of the feasible power-flow solution is proved. Moreover, the iterative algorithm of the feasible power-flow solution is proposed, which is proved to be monotonically exponentially convergent. The proposed algorithm's domain of attraction is derived, thus, the initial iterative value of which can easily be chosen to guarantee its convergence. Finally, case studies are given in this paper to verify the correctness and effectiveness of the proposed theorems.